TINJAUAN PRINSIP-PRINSIP DEMOKRASI DALAM HUKUM ISLAM - Lukman Hakim (JURNAL CERDAS HUKUM, 2023)
Islamic relations with democracy to this day are still a topic often discussed by Islamic scholars. Some consider that democracy cannot be united with Islam, because democracy is not part of the product of Islam, but rather the product of the West. Others accept and argue that democracy is in line with Islam. Because democratic principles are also found in the teachings of Islam. Nevertheless, the debate is still frequent and the ikhtilaf among Islamic figures cannot be united. It attempts to explain the concept of piqih's proposal as a means of bridging or seeing how the correlation and relationship between democracy and piqih thinking and comprehensive Islamic law are. Because when a normative law is not found in the Qur'an and hadith, then the ijtih space and the rule of piqih are allowed to give the answer to the problems faced by Muslims. And the idea of a democratic relationship with Islam will be answered using the piqih proposal approach. As long as democracy does not conflict with Islam then democracy does not conflict with Islam